Procedural Law Dualism in Asset Forfeiture Regime: Conflict of Evidentiary Norms and Judicial Oversight Regarding Human Rights Protection - Asep Dadang Herdiana (CV. Social Politic Genius (SIGn), 2025)
Corruption as an extraordinary crime demands progressive asset recovery instruments through the Asset Forfeiture Bill, yet its planned enactment may create procedural law dualism after the effective date of Law Number 20 of 2025. This research aims to analyze the disharmony in evidentiary standards, the expansion of seized-object definitions based on illicit enrichment, and the implications of shifting judicial oversight for the existence of the Pretrial institution as a guardian of human rights protection. Using the normative legal research method with statutory and conceptual approaches, the analysis is conducted through a qualitative prospective compatibility test. The results show a highly significant norm antinomy, where the reversed burden of proof mechanism in the Asset Forfeiture Bill diametrically opposes the presumption of innocence principle and the negative statutory proof system (negatief wettelijk) as regulated in Law Number 20 of 2025. Furthermore, the expansion of forfeiture object criteria ignoring the material connectivity boundaries of seized objects and the shifting of the objection mechanism to the internal executive are deemed to degrade judicial dignity and violate due process of law principles. The research conclusion asserts that without systemic harmonization placing the draft special regulation as a subsystem of the general regulation, the application of the lex specialis derogat legi generali principle will trigger destructive legal uncertainty. Therefore, harmonization of the substance of the Asset Forfeiture Bill with the human rights protection corridor in Law Number 20 of 2025 is an absolute prerequisite to prevent abuse of the exception loophole in Article 367 of the Law, while ensuring a balance between state asset recovery efficiency and citizens’ property rights protection.